Mathematical model of non-stationary temperature distribution in the metal body produced by induction heating process - Rak, Josef (EDP Sciences, 2016)
An induction heating problem can be described by a parabolic differential equation. For this equation, specific Joule looses must be computed. It can be done by solving the Fredholm Integral Equation of the second kind for the eddy current of density. When we use the Nyström method with the singularity subtraction, the computation time is rapidly reduced. This paper shows the method for finding non-stationary temperature distribution in the metal body with illustrative examples.
Matematický model nestacionárního rozložení teploty v tělese při indukčním ohřevu
Keywords: induction heating, integral equation of the second kind,non-stationary temperature distribution, Nyström method; indukční ohřev, integrální rovnice druhého druhu, nestacionární rozložení teploty, Nystromova metoda